4z+2-2z=3+z+6

Simple and best practice solution for 4z+2-2z=3+z+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4z+2-2z=3+z+6 equation:


Simplifying
4z + 2 + -2z = 3 + z + 6

Reorder the terms:
2 + 4z + -2z = 3 + z + 6

Combine like terms: 4z + -2z = 2z
2 + 2z = 3 + z + 6

Reorder the terms:
2 + 2z = 3 + 6 + z

Combine like terms: 3 + 6 = 9
2 + 2z = 9 + z

Solving
2 + 2z = 9 + z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1z' to each side of the equation.
2 + 2z + -1z = 9 + z + -1z

Combine like terms: 2z + -1z = 1z
2 + 1z = 9 + z + -1z

Combine like terms: z + -1z = 0
2 + 1z = 9 + 0
2 + 1z = 9

Add '-2' to each side of the equation.
2 + -2 + 1z = 9 + -2

Combine like terms: 2 + -2 = 0
0 + 1z = 9 + -2
1z = 9 + -2

Combine like terms: 9 + -2 = 7
1z = 7

Divide each side by '1'.
z = 7

Simplifying
z = 7

See similar equations:

| -13+x=x+24 | | 314=13(x-2)-(12x-13)-2(150+x) | | -7(y+2)=1-6y | | 11x+6=9999999999999999999999999999999999999999999999999999999999888888888888888887 | | .5(2x-6)-2(3x+1)=10 | | 5z-7=7z-3z | | -8-9=3x+5+2x | | 1/2(5x+9)=7x | | 10=6x-7 | | 7-5z=32 | | -8(2t-(4-7))= | | (3y+2)dx-(5x-7)dy=0 | | 15x+-10=-9x+2 | | -9x-9y=0 | | 1=0.4x-0.6x-17 | | 4x+3x-6-6=10+3 | | 3x^2=3-4x | | -3n+5n=38 | | x=2500-5x | | 3.5-h=42 | | w=y(r+A) | | 3.5+42=h | | 14k-5=65 | | z+9=126 | | 183/5+29/28-11/28 | | 5+105(2d-1)=.5 | | 6s-14=-6s+5 | | 8+11t-5=6t+66-4t | | 3.5+h=42 | | -8x-x+5=-6+5-3x | | T^3+12t^2-2t-24=0 | | 3x-121 |

Equations solver categories